2022
DOI: 10.3389/fphar.2022.969883
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometrics and visualization analysis of cannabidiol research from 2004 to 2021

Abstract: Cannabidiol, a non-psychoactive component extracted from the plant cannabis sativa, has gained growing focus in recent years since its extensive pharmacology effects have been founded. The purpose of this study intends to reveal the hot spots and frontiers of cannabidiol research using bibliometrics and data visualization methods. A total of 3,555 publications with 106,793 citations from 2004 to 2021 related to cannabidiol were retrieved in the Web of Science database, and the co-authorships, research categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Bibliometric analysis will be conducted using specialized software such as VOSviewer or CiteSpace. These tools facilitate the visualization of bibliometric networks, including co-citation, co-authorship, and keyword cooccurrence analyses [53].…”
Section: Discussionmentioning
confidence: 99%
“…Bibliometric analysis will be conducted using specialized software such as VOSviewer or CiteSpace. These tools facilitate the visualization of bibliometric networks, including co-citation, co-authorship, and keyword cooccurrence analyses [53].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to review the The results showed that cannabidiol was a complex research object that was studied concerning various aspects of health and disease. However, it was evident that the harmful effects and toxicity of cannabidiol were not sufficiently studied (only 3.21%), and therefore further research was needed [7].…”
Section: Analysis Of Chemical Pharmacodynamic and Pharmacokinetic Fea...mentioning
confidence: 99%
“…Figure 1. Visualisation of research areas on the effects of cannabidiolSource: compiled by the author based on[7] …”
mentioning
confidence: 99%
“…Another software tool CiteSpace offers a wealth of parameter settings and customisation options, allowing users to utilise flexible settings and perform analyses according to their own research needs. Furthermore, bibliometric and visual analyses enable the illustration of textual information in terms of the contributions and collaborations of different countries or regions, institutions, journals, and authors, improving the interpretability of this information ( Liu L et al, 2022 ). Both these software were used in this study, enhancing the presentation and accuracy of the data analysis.…”
Section: Introductionmentioning
confidence: 99%